2000
DOI: 10.1007/s100380070031
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphisms in the hMSH3 gene and sporadic colon cancer with microsatellite instability

Abstract: The association between three single nucleotide polymorphisms (SNPs) in the hMSH3 gene and sporadic colon cancer with microsatellite instability (MSI) was analyzed. Of the three SNPs observed in this population, SNPs at residues 235 and 693 were novel, while that at residue 3133 was previously described. The SNPs at residues 235 and 3133 caused amino acid substitutions, V79I and T1045A, respectively. We analyzed the allele frequencies of the three SNPs in samples from 19 patients with sporadic colon cancer wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…All variants were also found among healthy blood donors, essentially excluding mutations with high penetrance specific to either sporadic or hereditary CRC. On the constitutional DNA level, the three common missense variants (V70I, R940Q, and T1036A) have been associated with risk modification for colorectal cancer [39,40]. The hereby newly identified L902W missense variant presents the only one amino acid change so far reported that is predicted to be functionally based on homology.…”
Section: Discussionmentioning
confidence: 95%
“…All variants were also found among healthy blood donors, essentially excluding mutations with high penetrance specific to either sporadic or hereditary CRC. On the constitutional DNA level, the three common missense variants (V70I, R940Q, and T1036A) have been associated with risk modification for colorectal cancer [39,40]. The hereby newly identified L902W missense variant presents the only one amino acid change so far reported that is predicted to be functionally based on homology.…”
Section: Discussionmentioning
confidence: 95%
“…In an investigation, Wu et al (2001) determined 12 missense SNPs in the EXO1 gene; one of them is the P757L polymorphism in exon 13. Although polymorphisms in several genes have been studied in relation to CRC (Orimo et al, 2000;Toffoli et al, 2003;Adleff et al, 2004), few surveys have been conducted to determine the association between polymorphisms in the EXO1 gene and CRC risk (Wu et al, 2001;Bau et al, 2007Bau et al, , 2008Chiu et al, 2008;Jin et al, 2008;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…17 They also found three SNPs in the MSH3 gene and frequency of the G693 (G/A) allele was high in sporadic colon cancer patients. 18 Song et al systematically investigated all the common genes in the MMR system and confirmed the effect of SNPs on ovarian cancer risk. In their study, MSH3 SNPs were not associated with the risk of ovarian cancer.…”
Section: Discussionmentioning
confidence: 94%